Strengthening the atom-field coupling through the deep-strong regime via pseudo-Hermitian Hamiltonians - de Ponte, M. A. [UNESP]; de Oliveira Neto, F.; Soares, P. M.; Moussa, M. H.Y. (Stichting SciPost, 2023)
We present a strategy for strengthening the atom-field interaction through a pseudo- Hermitian Jaynes-Cummings Hamiltonian. Apart from the engineering of an effective non-Hermitian Hamiltonian, our strategy also relies on the accomplishment of short-time measurements on canonically conjugate variables. The resulting fast Rabi oscillations may be used for many quantum optics purposes and specially to shorten the processing time of quantum information.